A Pilot Study of MicroRNAs Expression Profile in Serum and HBsAg Particles: Predictors of Therapeutic Vaccine Efficacy in Chronic Hepatitis B Patients. Issue 2 (January 2016) - Wang, Weixia; Li, Jin; Zhang, Xiaonan; Wen, Yumei; Wang, Xuan-Yi; Yuan, Zhenghong
Abstract : Abstract: Chronic hepatitis B (CHB) remains a global health problem. Therapeutic vaccination has been successfully employed to treat a subpopulation of CHB patients. Personalized treatment can not only improve therapeutic efficacy, but also decrease the cost of medical care. Since microRNAs (miRNAs) are highly conserved and are involved in many cellular processes, exploring their expression profiles in CHB patients in association with responsiveness to therapeutic vaccination may be an approach for personalized treatment. In this study, we examined the kinetic expression profiles of 13 miRNAs in sera and serum-derived hepatitis surface antigen (HBsAg) particles in 10 CHB patients including 5 responders and 5 nonresponders selected from a large cohort of 136 patients enroled in a phase III clinical trial using antigen-antibody immunogenic complex based therapeutic vaccine (YIC). Eight miRNAs were detected in both sera and HBsAg particles. Among them, the levels of serum miRNAs and serum-derived HBsAg-carried miRNAs (let-7f, miR-22, miR-30a, and miR-122) were significantly lower in the responders group compared to those in the nonresponders group at baseline and throughout the course of treatment. The lower baseline levels of serum miRNAs and HBsAg-carried miRNAs were also associated with hepatitis e antigen clearance at week 76 and hepatitis e antigen seroconversion during the study period. In summary, our study suggests that lower baseline levels of serum miRNAs and HBsAg-carried miRNAs (let-7f, miR-22, miR-30a, and miR-122) associated with YIC treatment response and the variation trend of these 4 miRNAs could have a prognostic value for responsiveness to YIC treatment. Abstract : Supplemental Digital Content is available in the text